Komparasi interior rumah tradisional Nusantara: Rumah Joglo Yogyakarta Indonesia dan Rumah Melaka Malaysia - Anggriani, Swastika Dhesti; Ponimin; Sidyawati, Lisa; Ujang, Norsidah (Institut Seni Budaya Indonesia, 2023)
This research aims to determine the differences and similarities between the traditional houses of the archipelago with research samples taken from two countries, namely the Indonesian Joglo house and the Malaysian Melaka house. The research method used is comparative study of Nusantara’s traditional houses. Data obtained for this research are collected by direct observation to the location (Yogyakarta and Malaysia), interviews, and taking data in documents in the form of photos, layout drawings, and visible images. In terms of the building aspect, the Joglo house is built directly above the ground level, while the Melaka house is built on a stilt system. Different types of buildings and their users and spatial activities lead to differences in interior spatial layouts. However, both the Joglo house and the Melaka house were built in single building mass. The two houses were built using wood materials on the walls, poles, and roofs.